THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF STIMULATIONS BY PARENTS AND THE DEVELOPMENT OF TODDLER AGED 24-36 MONTHS - Hany Lismaya Priyani; Dede Gantini; Ir Ir Khairiyah (Poltekkes Kemenkes Semarang, 2019)
Background. Stimulations are important in the golden period (age 0-3). Children who receive directional stimulation will develop more quickly than children who have less or no stimulation.Purpose. The purpose of this study was to determine the relationship between the implementation of stimulations by parents and the development of toddlers aged 24-36 months in Bungursari Village.Methods. This research was an observational quantitative research with cross-sectional approach. The populations were mothers and toddlers aged 24-36 months as many as 92 respondents. The sampling technique was simple random sampling, with a total sample of 42 respondents.Results. The results showed that the largest percentage in the implementation of gross motor stimulation, fine motor skills, speech and language skills, social skills and independence by parents were in the frequent category, the largest percentage of toddler development aged 24-36 months according to the appropriate category. Spearman rank statistical test results obtained rho value of 0.417 with p value of 0.006, where p value was less than α (0.006 0.05), this showed that there was a positive relationship between the implementation of stimulations by parents on the development of toddler.Conclusion. There was a relationship between the implementation of stimulations by parents and the development of the toddlers. It is suggested to involve parents in conducting stimulation and development screening in order to improve their growth and development.